Islamic Education Portfolio Evaluation System And Its Relevance To Era 5.0 Independent Curriculum Learning - Khoir, Qoidul; Margarida, Kruger; Marlina, Marlina; Xavier, Embrechts; Zulaekah, Zulaekah (Journal Neosantara Hybrid Learning, 2024)
With the emergence of the Era 5.0 independent curriculum which emphasizes personal and holistic learning, evaluation of Islamic education needs to be adjusted so that it can measure a student's competency achievement in a comprehensive and sustainable manner. It is hoped that the development of an Islamic education portfolio evaluation system can facilitate a learning process that provides room for the progress of individual students. This research aims to analyze the relevance of the Islamic education portfolio evaluation system with the learning principles of the Era 5.0 independent curriculum and to identify the benefits and challenges in its implementation in educational institutions. The research methods used are literature study, observation, and interviews with Islamic education experts and curriculum development practitioners. Data was collected and analyzed to evaluate the success of implementing the Islamic education portfolio evaluation system in the context of the Era 5.0 independent curriculum. The research results show that the Islamic education portfolio evaluation system plays an important role in supporting learning in the Era 5.0 independent curriculum. This evaluation system provides opportunities for students to express their understanding of Islamic teachings creatively and contextually, and allows educators to track individual student development. The implementation of this research states that the Islamic education portfolio evaluation system has strong relevance to Era 5.0 independent curriculum learning because it is able to accommodate personal, holistic and progressive learning principles. To ensure successful implementation, comprehensive efforts are needed to develop fair and accurate assessment guidelines, as well as training for educators in consistently assessing portfolios. Thus, developing an Islamic education portfolio evaluation system can be a significant contribution in realizing learning objectives that are in line with the demands of the Era 5.0 independent curriculum